Identification of faults of the hybrid electric vehicle - Prykhodko, А.; Nikulin, D.; Приходько, О. Д.; Нікулін, Д. В.; Приходько, А. Д.; Никулин, Д. В. (Харківський національний автомобільно-дорожній університет, 2014)
A new innovative method of hybrid vehicle diagnostics by spectral analysis of the supply current.
Ідентифікація несправностей електроприводу гібридного автомобіля
Идентификация неисправностей электропривода гибридного автомобиля
Keywords: hybrid vehicle propulsion; electric drive; spectrum analysis; simulation model of the drive; Fast Fourier transform; силова установка гібридного автомобіля; електропривод; спектральний аналіз; імітаційна модель електроприводу; швидке перетворення Фур’є; силовая установка гибридного автомобиля; электропривод; спектральный анализ; имитационная модель электропривод; быстрое преобразование Фурьэ; 621.318